IMPLEMENTING GUIDED QUESTION TECHNIQUE TO INCREASE STUDENTS’ WRITING SKILL - Syaifudin Latif Darmawan; Ani Andrianti (Fakultas Keguruan dan Ilmu Pendidikan | Universitas Islam As-Syafi'iyah, 2019)
This study is classrom action research. It is carried out at SMP N 2 Metro in Academic Year of 2017/2018. The objectives of the research: (1) to find out whether guided question technique can increase the students’ writing skill in descriptive text; (2) to describe the process of teaching writing using guided question technique. The population of the research is the seventh grade students of SMP N 2 Metro in academic year 2017/2018 that consist of 32 students. The research is conducted in two cycles. The procedure of the research consists of identifying the problem, planning the action, implementing the action, observing the action, and reflecting the result of the research. Qualitative data are collected through interview, observation. In the meantime, quantitative data are collected through test. To analyze qualitative data, the researchers use miles and huberman model. It consists of three steps: data reduction, data display and data conclusion. Meanwhile, to analyze quantitative data, the researchers employ descriptive statistic. The result of the research indicates that the implementation of guided question technique improved the students’ writing skill in descriptive text. The average score of pre-test is 56. In the cycle 1, the researchers giving the treatment and get the students’ average score of post-test 1 is 69,23. After applying the revised planning in cycle 2, the average students’ score in post-test 2 is 76. It has reached 75% of 32 students that indicated the students passed the criterion of success. The result of students’ participation in cycle 1 and cycle 2 did a significant progress and improves in every meeting of each cycle. In addition, the use of guided questions technique is able to increase the students’ writing skill in descriptive text. The research has some suggestions; for the English teacher, it is useful to implement guided questions technique as one alternatives teaching, for the students it can be used to make the students easier in writing a text and for the further researcher this study can be used as a reference.